METODE PEMBELAJARAN KITAB KUNING - Maskuri Maskuri; Mohammad Kholison; Wildatul Islamiyah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
Every learning process, will never be separated from a method, as well as in learning the kitab kuning, because the method is one of the determinants of achieving maximum learning outcomes. So it is necessary to conduct an in-depth study related to the kitab kuning learning method and the stages in the kitab kuning learning. This study is set in the class of the Daru al-Kutub Education Foundation of the Bebidas Wanasaba Islamic Boarding School in East Lombok. By using a case study type qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this study are: first, the stages of learning the yellow book in the class include: dividing the students (santri) into several classes according to their level of ability, determining the books to be taught to students according to their level, and making rules. Second, the kitab kuning learning method in class is to use several methods commonly used in the kitab kuning learning process, such as the sorogan, bandongan, memorization, and mudzakarah methods, as well as holding weekly evaluations and monthly evaluations.